Vitrification method in banking of cord blood mononuclear cells - Çilingir, Özlem Tuğçe; İrez, Tülay and Taşyürekli, Mustafa and Bilgiç Gazioğlu, Sema (Cerrahpaşa Medical Journal, 2019)
Objectives: The idea of protection of stem cells in a cord blood bank for treatment of various diseases, becomes more widespread. The methods when used during the protection, must be developed for minimizing the risk of cell lost. According to our purpose, we made a comparison by using different protection methods for the cord blood stem cells, during the experiments. Methods: “Density-gradient” method was used for mononuclear cell separation from cord blood, which is taken from voluntary donors. We applied 2 different vitrification method. One of them consist of two steps. Before and after the freezing process, cell viabilities by trypan blue dye method, differences in CD34+, CD45+ and CD34+45+ cells ratio by flow cytometry method and, differences in morphology by light microscope had been determinated. Results: According to our experiment results, CD45+, CD34+ and CD34+/45+ cell ratios significantly decreased after vitrification processes. But there is no significant differences between 2 different vitrification method, we used. In the light microscopy analysis, cell membran structures have damaged, cells have seen like swell and cells come together and have seen attaching. Conclusion: Vitrification methods are usefull for cell banking because of their short, cheap and easy process. We are thinking that our study is helpful for improving new and suitable methods.